Co-creating social licence for sharing health and care data. (May 2021) - Fylan, Fiona; Fylan, Beth
Highlights: There is strong support for sharing health and care data for direct care. People are reluctant for their data to be used in commercial research. Concerns include being identified, security, and lifestyle-related care rationing. Co-creation groups developed a set of principles for a social licence for data sharing. Abstract: Background: Optimising the use of patient data has the potential to produce a transformational change in healthcare planning, treatment, condition prevention and understanding disease progression. Establishing how people's trust could be secured and a social licence to share data could be achieved is of paramount importance. Methods: The study took place across Yorkshire and the Humber, in the North of the England, using a sequential mixed methods approach comprising focus groups, surveys and co-design groups. Twelve focus groups explored people's response to how their health and social care data is, could, and should be used. A survey examined who should be able to see health and care records, acceptable uses of anonymous health and care records, and trust in different organisations. Case study cards addressed willingness for data to be used for different purposes. Co-creation workshops produced a set of guidelines for how data should be used. Results: Focus group participants (n = 80) supported sharing health and care data for direct care and were surprised that this is not already happening. They discussed concerns about the currency and accuracy of their records and possible stigma associated with certain diagnoses, such as mental health conditions. They were less supportive of social care access to their records. They discussed three main concerns about their data being used for research or service planning: being identified; security limitations; and the potential rationing of care on the basis of information in their record such as their lifestyle choices. Survey respondents (n = 1031) agreed that their GP (98 %) and hospital doctors and nurses (93 %) should be able to see their health and care records. There was more limited support for pharmacists (37 %), care staff (36 %), social workers (24 %) and researchers (24 %). Respondents thought their health and social care records should be used to help plan services (88 %), to help people stay healthy (67 %), to help find cures for diseases (67 %), for research for the public good (58 %), but only 16 % for commercial research. Co-creation groups developed a set of principles for a social licence for data sharing based around good governance, effective processes, the type of organisation, and the ability to opt in and out. Conclusion: People support their data being shared for a range of purposes and co-designed a set of principles that would secure their trust and consent to data sharing.